Диференційні особливості дифузних змін головного мозку у хворих на діабетичну енцефалопатію залежно від типу основного захворювання - Пашковська, Н. В. (Clinical Endocrinology and Endocrine Surgery, 2008)
Differential peculiarities of diffuse brain abnormalities were investigated according to the data of computerized and magnetic resonance tomography in patients with diabetic encephalopathy in dependence on the type of basic disease. It was established, that in patients with diabetic encephalopathy the linear parameters of brain ventricles and subarachnoidal spaces were elevated significantly. The signs of internal hydrocephaly were more obvious in patients with diabetic encephalopathy in type 2 diabetes, and cerebral atrophy had equal manifestation degrees in both — insulindependent and non-insulindependent diabetes.